Development of Machined Durable Parts of Modified 110g13l Brand Steel - Turakhodjaev Nadir Dzhakhangirovich; Chorshanbiev Shukhrat Makhmatmurodovich; Tadjiev Nuriddin Khusniddinovich (Genius Publishing Group, 2023)
This article provides great opportunities for the modification of steel in improving the quality of steel, reducing the amount of harmful impurities and methods of processing outside the furnace, which allow to seriously affect the quantity, composition, shape and distribution of non-metallic inclusions. The quality of Steel is significantly more deeply influenced by special electrometallurgical methods. These methods are widely used in obtaining high-quality steel castings. The simplest method of processing steel outside the oven is modification. Modified carbon steel is much more economical in properties-terjab approaches leached steel, while modified steel leached by saving and investigation approaches leached steel with valuable and rare additives (Ni, mo and other). Modification with alkaline and alkaline-earth metals greatly increases the quality of steel. The quality of Steel is positively influenced by nitride-forming modifiers
Keywords: Modifier; carbon; alloy; crystallization